Factors for Emprowering UMKM in Maintaining Sustainable Bio Economy - Saparuddin Mukhtar; Kikin Yuliaty Subarsa Putri; Samadi (Future Science)
The economic empowerment of the Indonesian people has been carried out through UMKM. Indonesian people are still learning in economic empowerment through UMKM in various aspects. The formulation of research problems is the factor of empowering UMKM in maintaining sustainable bioeconomics? The purpose of this study is to analyze the factors of empowering any UMKM in maintaining a sustainable bio-economy. The concept used in research is community economic empowerment is a community skill in managing their economic efforts well. The method used is quantitative by distributing questionnaires to 93 respondents in several major cities in Indonesia. Reflective descriptive research is all positive in empowering UMKM in the community. The most influential factor in community economic empowerment is making the community more independent. The smallest value dimension is the occurrence of structural changes in the economy. Suggestion for research is that all aspects of society should help empower UMKM communities so that society does not depend on the system implemented by the government.